Challenges and the direction of legal politics after the abolition of the presidential threshold in Indonesia’s democratic system - Maris Zayyanurroihan; Ardian Mulyadi; Muhammad Zaenul Arif (Institute Of computer Science (IOCS), 2024)
The abolition of the Presidential Threshold in Indonesia's presidential election system has significant implications for the configuration of political power, the dynamics of the party system, and the direction of national legal politics. The presidential threshold has long been regarded as a political instrument that restricts democratic space, limits citizen participation, and strengthens party oligarchy. In practice, the threshold has hindered the emergence of alternative candidates outside major coalitions, resulting in stagnation in national leadership regeneration. Once this provision is abolished either through judicial rulings or legislative reform Indonesia faces a major challenge in maintaining a balance between political openness and governmental stability. This article aims to examine the political and legal challenges following the abolition of the threshold and to formulate a relevant legal-political direction within the context of constitutional democracy. Using a qualitative approach through normative-juridical methods and legal-political analysis, this study finds that the abolition of the threshold must be accompanied by electoral system reform, the strengthening of democratic institutions, and the development of a presidential candidate selection mechanism that is democratic, accountable, and responsive to public aspirations. Future legal politics must serve as an instrument for the transformation of substantive democracy, rather than merely adapting to procedural changes.